Pelatihan Pembuatan MPASI dengan Memanfaatkan Aplikasi Baby Meal Planner pada Kader Posyandu di Babakan, Bogor Tengah - Annisa Kartinawati; Annisa Rizkiriani; Rosyda Dianah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Babies must be given complementary food for ASI (MP ASI) when they are 6 months old, to be able to meet their energy and nutritional needs. However, there are still many mothers who do not have enough knowledge in making MP ASI. The purpose of this activity is to train posyandu cadres in making MP ASI by utilizing an Android Base Application, Baby Meal Planner (BMP). The activity was carried out on 5‒7 October 2021 in the Babakan Village, Central Bogor District, Bogor City. The activity participants totaled 13 posyandu cadres from 7 RWs in the Village. The activity consists of 3 stages. The first stage is training in the form of pretest activities, material presentation, discussion, posttest, and MPASI menu planning assignments, the second stage is assistance in the form of participant activities to re-teach the knowledge gained on the first day, to mothers of babies who are members of Posyandu, the third stage is evaluation in the form of competition activities processing MP ASI. After attending this training, there was an increase in knowledge of 30% and skills of 14% for posyandu cadres in making MP ASI using the BMP application.